Growing Potatoes in the Florida Home Garden - Jeffery E. Pack; James M. White; Chad M. Hutchinson (EDIS)
One cannot truly appreciate the taste of a good potato until you grow and prepare it on your own. A recently grown and harvested potato tastes very different from one that has been in storage or on a grocery shelf for up to 6 months or more, and it is a very satisfying discovery to make.This document is HS933, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: July 2003.